Design And Testing Of Patient-Specific Ankle Foot Orthosis - Md Sukri, Muhammad Ahnaf Ataulah (Universiti Sains Malaysia, 2022)
Abnormal gait is a common foot deformity where the patient is unable to move his forefoot during stance and walking position due to involuntary plantarflexion. An ankle-foot orthosis is a medical device worn to assist the daily mobility of patients suffering from ankle-foot deformity because of stroke or accident. However, the available product in the market was costly, and the design was not suitable for local patients due to the hot and humid tropical climate. The currently available product also does not fit perfectly to a specific patient’s foot profile, resulting in discomfort and therefore less usage by the patient. In this research, two types of Ankle Foot Orthosis (AFO) devices have been successfully developed. Two AFO models, which are Type 1 (Hybrid AFO) and Type 2 (Hinged AFO) were fabricated by using Creality Ender 5 machine utilising 3D printing and 3D scanning technologies. Apart from that, two other models Type 3 and Type 4, from previous work by Yong Shien also have been taken for gait analysis purposes which is the main interest in this research. The gait analysis is conducted as a pilot clinical study of the AFO performance in the rehabilitation process in Hospital USM. In the study, two patients have been tested with the devices to evaluate the performance of each AFO. It is found that the use of any AFO devices can improve a patient’s gait deformity during the rehabilitation program. The result shows that Type 2 (Hinged AFO) improved gait cycle time [CI = 95%; Without AFO vs. With AFO; 3.58 ± 0.18 vs. 2.92 ± 0.21 s; p = 0.0302] for active patients, while there is no significant difference between the effectiveness of the Hinged AFO in enhancing the gait performance of a passive patient during the rehabilitation therapy (CI = 95%; Without AFO vs. With AFO; 4.05 ± 0.49 vs. 4.07 ± 0.63; p = 0.32). This, suggests that in the case of an active patient, both types of AFO are suitable and produce a significant improvement, while solid AFO is more suitable to improve the gait parameters for the passive patient with a significant difference of (p = 0.025). A further clinical trial will be required to further investigate the efficacy of the devices to sub-acute stroke patients in developing a fully functional ankle foot orthosis for lower limb rehabilitation therapy.